Job Satisfaction and Gender: A Global Comparison of Job Satisfaction in the Hospitality Industry. Issue 3 (4th May 2022) - Andrade, Maureen Snow; Miller, Doug; Westover, Jonathan H.
ABSTRACT: Research has been inconclusive in determining if men or women experience more job satisfaction. A global comparison examining extrinsic and intrinsic factors, work relations, and work–life balance determinants found few differences; however, work relations and work–life balance factors were more significant for male than female workers across occupations. The current study uses International Social Survey Program data representing 37 countries to explore differences in job satisfaction in the hospitality industry. Findings demonstrate that mean job-satisfaction scores for females are lower across hospitality occupations except for hotel receptionists, housekeeping supervisors, and hotel cleaners. Regression results revealed additional differences such as the significance of coworker relations, the negative impact of being discriminated against and harassed at work, working weekends, marital status, and supervisory status for women with autonomy, work stress, education, and employment relationship being more salient for men. Interesting work, work being useful to society, job security, pay, relations with management, and work interfering with family were significant for both males and females.